Recovery and transport of industrial waste heat for their use in urban district heating and cooling networks using absorption systems - Atienza-Márquez, Antonio; Bruno, Joan Carles; Coronas, Alberto (MDPI, 2020)
The use of industrial excess heat in district heating networks is very attractive. The main issue is the transport of the heat from the point of generation to the local distribution network, in a way similar to the structure of electricity transport and distribution networks. Absorption systems have been proposed to transport and distribute waste heat using two absorption stations. In one of them (step-up station), industrial heat at a low temperature is pumped to a higher temperature to facilitate its transport and at the same time increase the temperature difference between the supply and return streams, in this way reducing the hot water mass flow rate circulating through the heat transport network. Heat is then used in a second absorption system (step-down station) to provide heat to a low temperature local district network. In this paper, several absorption system configurations are analyzed for both stations. A detailed thermodynamic analysis of each configuration is performed using selected energy performance indicators to calculate its global performance. The implementation of these kind of systems could enable the use of waste heat to produce heating and cooling for smart communities located a few dozens of kilometers away from industrial sites.
Keywords: Calor perdido; Ingeniería mecánica; Industrial waste heat; District heating and cooling; Absorption heat pump; Absorption heat transformers